2019
DOI: 10.1002/adfm.201904858
|View full text |Cite
|
Sign up to set email alerts
|

Charge‐Transport Properties of F6TNAP‐Based Charge‐Transfer Cocrystals

Abstract: The crystal structures of the charge-transfer (CT) cocrystals formed by the π-electron acceptor 1,3,4,5,7,8-hexafluoro-11,11,12,12-tetracyanonaphtho-2,6-quinodimethane (F 6 TNAP) with the planar π-electron-donor molecules triphenylene (TP), benzo[b]benzo[4,5]thieno[2,3-d]thiophene (BTBT), benzo[1,2-b:4,5-b′]dithiophene (BDT), pyrene (PY), anthracene (ANT), and carbazole (CBZ) have been determined using single-crystal X-ray diffraction (SCXRD), along with those of two polymorphs of F 6 TNAP. All six cocrystals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 78 publications
2
37
0
Order By: Relevance
“…These results imply that in BTBT-F m TCNQ hole transport along the DA stacks is less effective than along other directions, a feature similar to that we recently found for co-crystals based on the 1,3,4,5,7,8hexafluoro-11,11,12,12-tetracyanonaphtho-2,6-quinodimethane acceptor. 11 Experimentally, based on OFET device measurements, Sato et al 28 have found n-channel charge transport along the mixedstack direction in the BTBT-F m TCNQ (m = 0, 2, 4) single crystals, with the largest mobility of about 0.2 cm 2 V À1 s À1 observed in the case of BTBT-F 4 TCNQ. Tsutsumi et al 25 have also found predominately n-channel charge transport in OFET devices based on diC 8 BTBT-F m TCNQ (m = 0, 2, 4) co-crystals, with the largest electron mobility 0.4 cm 2 V À1 s À1 , measured along the DA stacks in diC 8 BTBT-F 2 TCNQ.…”
Section: Electronic Structurementioning
confidence: 99%
See 1 more Smart Citation
“…These results imply that in BTBT-F m TCNQ hole transport along the DA stacks is less effective than along other directions, a feature similar to that we recently found for co-crystals based on the 1,3,4,5,7,8hexafluoro-11,11,12,12-tetracyanonaphtho-2,6-quinodimethane acceptor. 11 Experimentally, based on OFET device measurements, Sato et al 28 have found n-channel charge transport along the mixedstack direction in the BTBT-F m TCNQ (m = 0, 2, 4) single crystals, with the largest mobility of about 0.2 cm 2 V À1 s À1 observed in the case of BTBT-F 4 TCNQ. Tsutsumi et al 25 have also found predominately n-channel charge transport in OFET devices based on diC 8 BTBT-F m TCNQ (m = 0, 2, 4) co-crystals, with the largest electron mobility 0.4 cm 2 V À1 s À1 , measured along the DA stacks in diC 8 BTBT-F 2 TCNQ.…”
Section: Electronic Structurementioning
confidence: 99%
“…Over the last two decades, p-conjugated organic materials have attracted considerable attention for potential applications in various optoelectronic devices [1][2][3][4][5] with organic donor-acceptor (DA) co-crystals being considered as promising materials for OFET (organic field-effect transistor) applications. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] In the case of binary molecular systems, the latter consist of a regular arrangement of D and A molecular moieties with a defined stoichiometry. Usually, DA co-crystals display a ground-state charge transfer (CT) configuration (D r+ -A rÀ ) with a partial ionicity.…”
Section: Introductionmentioning
confidence: 99%
“…Mixed stack ordered complexes were reported for combinations of F6TCNNQ with triphenyl, pyrene, phenanthracene, naphtho[1,2-b:5,6-b 0 ]dithiophene 47 or for BTBT, anthracene, carbazole, benzo[1,2-b:4,5-b 0 ]dithiophene. 50 On the basis of the presented data we assume that all shown EDA complex structures are referred to ordered complexes with mixed stacks, also called co-crystals. The strong CT absorption for DBTTF and F6TCNNQ co-deposited films might be a reason for the formation of other crystalline structures.…”
Section: Materials Advances Papermentioning
confidence: 99%
“…45,80 The molecular sizes for DIP in the high temperature bulk phase 80 give roughly the same unit cell parameters as the thin film phase. 82,83 The molecular sizes for the acceptors are taken from mixed crystals reported in literature 50,79 and compared to the single crystal data for F6CTNNQ. 41 Whereas DBTTF and the acceptors have quite similar sizes, DIP is larger along the long axis of the molecule.…”
Section: Paper Materials Advancesmentioning
confidence: 99%
“…In addition, Yu et al also achieved the ambipolar charge transport in cocrystals by assembling acceptors with donors of different aromatic conjugated backbones. With the aromatic conjugated backbone of donors increased, the energy levels of supramolecular hybrid orbitals in D/A pairs were higher, contributing to the CT interaction ( Zhang X. et al, 2018 ; Dasari et al, 2019 ). They synthesized four cocrystals using PDICNFN (PDICNF, N′-bis(perfluorobutyl)-1,7- dicyanoperylene-3,4:9,10-bis (dicarboximide) as the acceptor and anthracene, pyrene, perylene, and DPTTA as the donors ( Figure 4A ).…”
Section: Electronic Properties and Functionalitiesmentioning
confidence: 99%